A Critical Examination of Asian Students' Interracial and Interethnic Friendships at a Multiracial Urban School. (March 2021) - Wu, Ming-Hsuan
This study examines Asian students' interracial/interethnic friendships at a multiracial middle school. Friendship groups remain predominantly segregated despite the school's efforts, reflecting community and parental influences. The circulation of uncontested stereotypes such as "loud" and "brash" African Americans is based on normative ideas of communicative styles, making some Asian students hesitant to be friends with their African American peers. There also exists an Asian hierarchy where Chinese students look down upon Cambodian students who befriend African American students. This study demonstrates Asian students' construction of their social networks is inseparable from the construction of Whiteness in the broader society.